2013
DOI: 10.1017/s0007114513002432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the brown rice diet on visceral obesity and endothelial function: the BRAVO study

Abstract: Brown rice (BR) and white rice (WR) produce different glycaemic responses and their consumption may affect the dietary management of obesity. In the present study, the effects of BR and WR on abdominal fat distribution, metabolic parameters and endothelial function were evaluated in subjects with the metabolic syndrome in a randomised cross-over fashion. In study 1, acute postprandial metabolic parameters and flow-and nitroglycerine-mediated dilation (FMD and NMD) of the brachial artery were determined in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 43 publications
4
54
0
1
Order By: Relevance
“…To assess whether any one study had a dominant effect on the pooled RR, we performed leave-one-out sensitivity analysis, and its effect on the main summary estimate along with pertinent I 2 for heterogeneity was evaluated. We found that no single study markedly affected the summary estimate or p values for heterogeneity in T2DM, MetS, CHD, and stroke (eTable 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether any one study had a dominant effect on the pooled RR, we performed leave-one-out sensitivity analysis, and its effect on the main summary estimate along with pertinent I 2 for heterogeneity was evaluated. We found that no single study markedly affected the summary estimate or p values for heterogeneity in T2DM, MetS, CHD, and stroke (eTable 5).…”
Section: Resultsmentioning
confidence: 99%
“…We used the ‘leave-one-out’ method to evaluate whether any one study had a dominant effect on outcomes. Heterogeneity between the studies was evaluated using I 2 in which >50% suggest substantial heterogeneity. Due to the limited number of studies included in each analysis and/or substantial heterogeneity, we could not evaluate potential publication bias.…”
Section: Methodsmentioning
confidence: 99%
“…38 Participants were between 30 and 60-years-old males with metabolic syndrome. Brown rice reduced their post-prandial blood glucose level and insulin level.…”
Section: Medical Rice For Healthmentioning
confidence: 99%
“…Orz has been shown to reduce plasma cholesterol levels and hepatic intake [14,15]; hence, it can affect different cell functions in the human organism. A great variety of biological effects has been attributed to Orz, such as antidiabetic [16], antioxidant [1,17], and anti-inflammatory activities [18]. However, until recently, the most studied Orz-related activities include its hypolipidemic and anti-obesity effects [15,16,19,20].…”
Section: Introductionmentioning
confidence: 99%